Rapport annuel 1999. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
Rapport annuel du Conseil d'administration pour l'exercice clos le 30 avril 1999.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet